Protective and curative role of Spirulina platensis extracts on cisplatin induce acute kidney injury in rats. Issue 1 (2nd January 2019) - Zakaria, Mahmoud M.; El-Tantawy, Fatma Mohamed Mansour; Khater, Sherry Mohamed; Derbala, Safaa A.; Farag, Verginia Mohamed El-Metwally; Abdel-Aziz, Abdel-Aziz Fatouh
ABSTRACT: Cisplatin (Cp) is an anti-neoplastic drug. Nephrotoxicity is the major side effect of Cp. Spirulina (Sp) is a blue-green alga with the ability to alleviating side effects of chemotherapeutic drugs in clinic. The aim of the study was to evaluate the ability of Sp to protect from cisplatin-induced nephrotoxicity. Adult male rat was orally administered Sp two days before single dose of Cp over 21 days (Sp + Cp group), 2nd group that intake Sp two days after with the same dose of Cp (Cp + Sp group) and two further groups were served as controls treated with either Sp or Cp only, respectively, as well as normal healthy control was included. At the end of experiment, Cp drug was induced acute kidney injury elevated levels of BUN, creatinine, KIM-1, NGAL and microalbumin in significant compared to that of normal control group, while the opposite effects were found in the rats who received Sp only. Furthermore, the prophylactic group showed improvements in biochemical parameters compared to those received Cp only. The effects of Cp were found to be diminished in the treated group. In addition, evaluation of Bax and SIRT genes expression in combination with histomorphological alterations of the kidney indicated the protective effect of Sp against Cp. In conclusion, pretreatment with Sp protected Cp-induced nephrotoxicity, probably via its antiapoptotic properties.